Purified Monascus Pigments: Biological Activities and Mechanisms of Action - Husakova, Marketa; Patakova, Petra (Journal of natural products, 2025)
Monascus pigments having yellow, orange, and red colors are widely studied for their potential beneficial properties. Many different biological activities have been reported regarding Monascus pigments and their derivatives, but the usual method is to test complex extracts from the mycelium of the fungus or from a fungus-fermented substrate. However, this review is mainly concerned with the biological activities of purified Monascus pigments. Both yellow (ankaflavin, monascin) and red (rubropunctamine, monascorubramine) Monascus pigments are proven antioxidants if used in concentrations of 10 μg/mL or higher. Antimicrobial activity against Gram-positive and Gram-negative bacteria and fungi has been observed with all Monascus pigments. However, the best antimicrobials are red Monascus pigments, and their amino acid derivatives (l-cysteine derivatives have MIC 4 μg/mL against Enterococcus faecalis). Yellow monaphilones and orange monaphilols seem to have the highest anti-inflammatory activity (IC50 1.7 μM of monaphilol D) and, together with red Monascus pigment derivatives, have mild antiobesity and antidiabetic activities. Further, monascin and ankaflavin in daily doses of 0.5 and 0.08 mg, respectively, lowered serum blood levels of low-density lipoprotein cholesterol complexes in rats on a high-fat diet. Orange Monascus pigments, rubropunctatin and monaphilols A and C, exhibit cytotoxic and antitumor activities (IC50 8-10 μM).
Keywords: Animals; antiflogistika; Antioxidants; heterocyklické sloučeniny tricyklické; mikrobiální testy citlivosti; flaviny; Molecular Structure; lidé; antiinfekční látky; Pigments, Biological; Flavins; Anti-Infective Agents; Anti-Bacterial Agents; biologické pigmenty; Heterocyclic Compounds, 3-Ring; molekulární struktura; grampozitivní bakterie; Microbial Sensitivity Tests; Monascus; Anti-Inflammatory Agents; antioxidancia; zvířata; antibakteriální látky; Gram-Positive Bacteria; Humans